2010
DOI: 10.1097/bpb.0b013e3283320c31
|View full text |Cite
|
Sign up to set email alerts
|

Risk of recurrent dislocation and avascular necrosis after proximal femoral varus osteotomy in children with cerebral palsy

Abstract: A retrospective review was conducted on 50 children with cerebral palsy, having 89 femoral varus osteotomy at an average age of 7.4 years, trying to identify risk factors for complications, particularly redislocation and avascular necrosis. Among the well-reduced hips, new subluxation developed in 12 cases; postoperative radiographic measurements showed a mean neck-shaft angle of 135 degrees and an acetabular slope of 32 degrees . Main risk factors for secondary dislocation seem to be insufficient correction o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
1
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(52 citation statements)
references
References 13 publications
2
47
1
2
Order By: Relevance
“…10,11,13,18,20,[28][29][30] A recent systematic review 31 on the subject revealed that most authors simply comment on the presence or absence of AVN in their complications, without further detail. Interestingly, the reported rates in our study as well as three others where AVN was the primary outcome measure are among the highest within the literature at 27% to 69%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…10,11,13,18,20,[28][29][30] A recent systematic review 31 on the subject revealed that most authors simply comment on the presence or absence of AVN in their complications, without further detail. Interestingly, the reported rates in our study as well as three others where AVN was the primary outcome measure are among the highest within the literature at 27% to 69%.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8][9] Reported complication rates for hip reconstructive surgery in patients with CP have varied dramatically (0% to 81%). 8,[10][11][12][13][14][15][16][17][18] There has been minimal attention paid to the development of avascular necrosis (AVN) as a complication of hip reconstructions. The incidence of AVN reported within the literature is in the range of 0% to 69%.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This branch was subject to operation-related complications, such as non-union, inaccurate correction, avascular necrosis, refracture below the plate, infection, and hematoma, 13,22 which were categorized into 'temporary' and 'permanent' complications. Each complication was branched into 'stable' and 'unstable' hips.…”
Section: The Concurrent Prophylactic Femoral Varization Osteotomy Branchmentioning
confidence: 99%
“…FVO for an unstable hip in CP ranges from 0 to 25%, [22][23][24] and the dislocation rate of a stable hip after a prophylactic FVO was believed to be lower; it was assumed that the baseline value of an unstable hip rate after a FVO for an unstable hip would be 10% 25 and that for a stable hip would be 5% (Table I). This rate was assumed to be the probability that the contralateral stable hip undergoing a prophylactic FVO would become an unstable hip.…”
Section: Probabilitiesmentioning
confidence: 99%